Analisis Peran Yayasan Wadah Titian Harapan Dalam Upaya Penanggulangan Stunting - Raisa Maulida; Wa Ode Asmawati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research discusses the role of the Wadah Titian Harapan Foundation in efforts to overcome stunting. Through a case study at the Wadah Titian Harapan Foundation (Wadah Foundation), this research shows that support from philanthropic institutions contributes significantly to increasing the knowledge and skills of health cadres in detecting and preventing stunting. Collaboration between philanthropic institutions, government and non-government organizations has also proven effective in increasing the effectiveness of training programs. These include activities that require PSDM personnel due to a lack of cadre capacity, as well as minimal PSDM knowledge. Therefore, Wadah conducts knowledge training regarding stunting for cadres by connecting them with stakeholders so that the program can be carried out well. The results of this research provide important insight into the role of philanthropic institutions in supporting health cadres and overcoming stunting in children under five, which shows that there is a reduction in stunting rates. Philanthropy is an act of love towards fellow human beings, involving donations of time, money and energy to provide assistance to others (Bawaqi, 2019). The support provided by the Wadah Foundation includes various knowledge regarding steps to prevent stunting.